Screening for syphilis by serology of Thai workers going abroad - Mayuna Srisupanant (2018)
Syphilis serology is a basic screening test for the manual workers who wish to go abroad. In this work, the authors summarize results and prevalence screening syphilis serology in Thai manual workers going aboard from a tertiary hospital in Thailand. Although these manual workers have healthy general appearance there are a considerable number of a rapid plasma regain (RPR) positive cases (0.83%). © 2009 Elsevier Ltd. All rights reserved.